Seizure-Induced Regulations of Amyloid-β, STEP61, and STEP61 Substrates Involved in Hippocampal Synaptic Plasticity - Sung-Soo Jang; Sara E. Royston; Gunhee Lee; Shuwei Wang; Hee Jung Chung (Neural Plasticity)
Alzheimer’s disease (AD) is a neurodegenerative disorder characterized by progressive cognitive decline. Pathologic accumulation of soluble amyloid-β (Aβ) oligomers impairs synaptic plasticity and causes epileptic seizures, both of which contribute to cognitive dysfunction in AD. However, whether seizures could regulate Aβ-induced synaptic weakening remains unclear. Here we show that a single episode of electroconvulsive seizures (ECS) increased protein expression of membrane-associated STriatal-Enriched protein tyrosine Phosphatase (STEP61) and decreased tyrosine-phosphorylation of its substrates N-methyl D-aspartate receptor (NMDAR) subunit GluN2B and extracellular signal regulated kinase 1/2 (ERK1/2) in the rat hippocampus at 2 days following a single ECS. Interestingly, a significant decrease in ERK1/2 expression and an increase in APP and Aβ levels were observed at 3-4 days following a single ECS when STEP61 level returned to the baseline. Given that pathologic levels of Aβ increase STEP61 activity and STEP61-mediated dephosphorylation of GluN2B and ERK1/2 leads to NMDAR internalization and ERK1/2 inactivation, we propose that upregulation of STEP61 and downregulation of GluN2B and ERK1/2 phosphorylation mediate compensatory weakening of synaptic strength in response to acute enhancement of hippocampal network activity, whereas delayed decrease in ERK1/2 expression and increase in APP and Aβ expression may contribute to the maintenance of this synaptic weakening.